1986
DOI: 10.1897/1552-8618(1986)5[69:ratpid]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ration and Toxicant Preexposure Influence Dieldrin Accumulation by Rainbow Trout (Salmo Gairdneri)

Abstract: Whole body accumulation and tissue distribution of dieldrin in rainbow trout were studied through oral-dose disposition tests and subchronic exposures via water (0.04 and 0.08 wg dieldrin/L) and/or diet (0.087 wg dieldrinig fishid). Growth and no-growth (maintenance) rations of 4 and 2% body weight per day were employed. In subchronic tests, apparent steady-state residue concentrations depended on ration and exposure concentration after 8 weeks of exposure. At 16 weeks, mean whole fish residue concentrations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Although we have discussed the roles of exploitation, level of energy input and competition sep arately in influencing toxicant performance, system responses to dieldrin including fish population extinctions resulted from complex interactions of all environmental and organizational factors functioning together Like toxicant effect, toxicant fate may be influenced by system organization and environmental conditions Near steady-state dieldrin tissue concentrations were different in fish from systems that differed in organization and environment and were similar in fish from systems having similar organization and environment Environmental factors affecting the amount of lipid in an organism have been shown to influence accumulation of lipophilic compounds [13,18] However, differences in quantity of lipid could only partially explain the observed differences in dieldrin concentrations in fish from our laboratory ecosystems When concentrations were expressed as dieldrin per gram lipid, differences between the systems were still apparent Shubat and Curtis [13] proposed that dieldrin ac cumulation in rainbow trout was correlated with the composition of lipid constituents in tissues and that qualitative changes in lipid could result from ration level and dieldrin treatment Although we did not attempt qualitative analysis of lipid constituents in fish tissues, Shubat and Curtis' proposal provides an interpretation of the observed dieldrin accumulation…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have discussed the roles of exploitation, level of energy input and competition sep arately in influencing toxicant performance, system responses to dieldrin including fish population extinctions resulted from complex interactions of all environmental and organizational factors functioning together Like toxicant effect, toxicant fate may be influenced by system organization and environmental conditions Near steady-state dieldrin tissue concentrations were different in fish from systems that differed in organization and environment and were similar in fish from systems having similar organization and environment Environmental factors affecting the amount of lipid in an organism have been shown to influence accumulation of lipophilic compounds [13,18] However, differences in quantity of lipid could only partially explain the observed differences in dieldrin concentrations in fish from our laboratory ecosystems When concentrations were expressed as dieldrin per gram lipid, differences between the systems were still apparent Shubat and Curtis [13] proposed that dieldrin ac cumulation in rainbow trout was correlated with the composition of lipid constituents in tissues and that qualitative changes in lipid could result from ration level and dieldrin treatment Although we did not attempt qualitative analysis of lipid constituents in fish tissues, Shubat and Curtis' proposal provides an interpretation of the observed dieldrin accumulation…”
Section: Discussionmentioning
confidence: 99%
“…The toxicant dilution and delivery system was similar to the continuous flow dilution apparatus described by Chadwick and Kiigemagi [12]. Nominal water concentrations of dieldrin were maintained by adjustment of the dilution apparatus following weekly gas chromatographic determinations of samples collected from the delivery system using procedures described by Shubat and Curtis [13]. Recovery was 83 k 14% (sE).…”
Section: Methodsmentioning
confidence: 99%
“…However, the presence of dieldrin residues in the tissues, eggs or milk of animals, exposed through diet to these chlorinated compounds (WHO-IPCS, 1989b), indicates that gastrointestinal absorption occurred at a significant extent in these species. In rainbow trout, given 0.32 to 5.7 µg/g fish per day of dieldrin the absorption via the gut was estimated to be between 34 and 10 % of the dose (Shubat and Curtis, 1986).…”
Section: Absorptionmentioning
confidence: 99%
“…CD pretreatment (5-15 mg/kg, ip) reduced hepatic concentrations and elevated other tissue [ 14 C]CD and [ 14 C]cholesterol levels in rodents (Carpenter & Curtis, 1989Gilroy et al, 1994). Similarly, long-term pretreatment of rainbow trout with dieldrin increased subsequent [ 14 C]dieldrin distribution to certain tissues, including liver and bile (Shubat & Curtis, 1986;Gilroy et al, 1993). Studies with trout liver slices concluded that dieldrin pretreatment (0.4 mg/kg/d in the diet for 10-12 wk) stimulated [ 14 C]dieldrin uptake and uptake and efflux of the PAH [ 3 H]-7,12-dimethylbenz[a]anthracene (DMBA; Gilroy et al, 1996).…”
mentioning
confidence: 99%